Developing bots with Microsoft Bots Framework : create intelligent bots using MS Bot Framework and Azure Cognitive Services /: create intelligent bots using MS Bot Framework and Azure Cognitive Services. (2017) - Machiraju, Srikanth; Modi, Ritesh
No abstract available